2012
DOI: 10.1088/0022-3727/45/4/045205
|View full text |Cite
|
Sign up to set email alerts
|

Time and spatially resolved LIF of OH in a plasma filament in atmospheric pressure He–H2O

Abstract: The production of OH in a nanosecond pulsed filamentary discharge generated in pin–pin geometry in a He–H2O mixture is studied by time and spatially resolved laser-induced fluorescence. Apart from the OH density the gas temperature and the electron density are also measured. Depending on the applied voltage the discharge is in a different mode. The maximum electron densities in the low- (1.3 kV) and high-density (5 kV) modes are 2 × 1021 m−3 and 7 × 1022 m−3, respectively. The gas temperature in both modes doe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
97
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 94 publications
(106 citation statements)
references
References 32 publications
6
97
2
1
Order By: Relevance
“…The decay time of the LIF signal then needs to be measured at each time together with the total LIF signal, to be able to correct the time dependent LIF signal (and thus OH density) for this. An example is shown in figure 2, for a high-density discharge in He + 0.84% H 2 O, with similar conditions as the discharge treated in [9]. In this case, the correction for time-resolved quenching changes the time-resolved OH density significantly.…”
Section: Oh Density Calibration Pitfallsmentioning
confidence: 93%
See 4 more Smart Citations
“…The decay time of the LIF signal then needs to be measured at each time together with the total LIF signal, to be able to correct the time dependent LIF signal (and thus OH density) for this. An example is shown in figure 2, for a high-density discharge in He + 0.84% H 2 O, with similar conditions as the discharge treated in [9]. In this case, the correction for time-resolved quenching changes the time-resolved OH density significantly.…”
Section: Oh Density Calibration Pitfallsmentioning
confidence: 93%
“…The authors have shown before that the self-destruction processes of OH are dominant in the loss of OH at the observed high OH density (see e.g. [9,39,40]). …”
Section: Time-resolved Oh Densitymentioning
confidence: 95%
See 3 more Smart Citations